DEVELOPMENT OF TAILINGS-BASED FORMULATIONS AS AN ENVIRONMENTALLY FRIENDLY BUILDING MATERIAL: A LABORATORY-SCALE STUDY IN MIMIKA REGENCY, CENTRAL PAPUA, INDONESIA - Nilam Sry Putri; Abd Rahim; Oktavianty Batto; Nurnaliza Mayalibit; Sony Patabang; Tony Ardiansyah (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2026)
Tailings management remains a persistent environmental challenge in mining regions, including Mimika Regency, Central Papua, Indonesia, where impoundment remains the dominant disposal practice. Building on prior geochemical and mineralogical characterization of local tailings, this study developed and evaluated three tailings-cement formulations, F1 (60:40), F2 (70:30), and F3 (80:20) tailings-to-cement ratio by mass, as candidate non-structural building materials. Specimens were cast as 50 mm cubes and tested for compressive strength at 7, 14, and 28 days, and for water absorption and density at 28 days, following procedures consistent with Indonesian National Standard SNI 03-0349-1989. Twenty-eight-day compressive strength reached 17.90 ± 0.57 MPa (F1), 12.21 ± 0.60 MPa (F2), and 7.23 ± 0.35 MPa (F3), with water absorption of 9.14-15.25% and density of 1.83-1.99 g/cm3. Formulations F1 and F2 satisfied Grade I, and F3 satisfied Grade II, of the applicable national standard for solid concrete brick used in wall construction, indicating that all three formulations, including the highest tailings substitution level tested (80%), are technically viable as non-structural building materials.